Therapy persistence in newly diagnosed non-valvular atrial fibrillation treated with warfarin or NOAC - Martinez, Carlos; Katholing, Anja; Wallenhorst, Christopher; Freedman, Saul Benedict (Thrombosis and Haemostasis, 2016)
Efforts to reduce stroke in atrial fibrillation (AF) have focused on increasing physician adherence to oral anticoagulant (OAC) guidelines, but high early vitamin K antagonist (VKA) discontinuation is a limitation. We compared persistence of non-VKA OAC (NOAC) with VKA treatment in the first year after OAC inception for incident AF in real-world practice. We studied 27,514 anticoagulant-naïve patients with incident non-valvular AF between January 2011 and May 2014 in the UK primary care Clinical Practice Research Datalink, with full medication use linkage: mean age 74.2 ± 12.4, 45.7 % female, mean follow-up 1.9 ± 1.1 years. After treatment initiation and follow-up until 1/2015, the proportion remaining on OAC at one year (persistence) was estimated using competing risk survival analyses. OAC was commenced ≤90 days after incident AF in 13,221 patients (48.1 %): 12,307 VKA and 914 NOAC (apixaban, dabigatran, rivaroxaban). Amongst those treated with OAC, the proportion commencing NOAC increased from zero in 1/2011 to 27.0 % in 5/2014, and OAC prescriptions for CHA2DS2VASc score ≥2 (guideline adherence) increased from 41.2 % to 65.5 %. Persistence with OAC declined over 12 months to 63.6 % for VKA and 79.2 % for NOAC (p< 0.0001). Persistence for those with CHA2DS2VASc ≥2 was significantly greater for NOAC (83.0 %) than VKA (65.3 %, p< 0.0001) at one year and all earlier time points. Comparison of VKA and NOAC cohorts matched on individual CHA2DS2VASc components showed consistent results. In conclusion, persistence was significantly higher with NOAC than VKA, and could alone lead to fewer cardioembolic strokes. Increased guideline adherence following NOAC introduction could further decrease AF stroke burden.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Atrial fibrillation; oral anticoagulants; persistence; NOAC; vitamin K antagonist